Recreational fishing pressure impacts the density and behaviour of the western rock lobster (Panulirus cygnus, George): evidence from small, no-take marine reserves. (8th October 2022) - Lindstedt, Daniel G; Langlois, Tim; Prince, Jane; de Lestang, Simon
Abstract: It is unknown whether lobster behaviour is sensitive to fishing, as has been previously suggested for fish. This study investigated the impacts of recreational fishing on the wariness of western rock lobster ( Panulirus cygnus, George) through comparisons between fished sites and no-take reserves (NTRs) at Rottnest Island. We used visual census to survey the density and size structure of lobster at sites inside and outside three comparable NTRs, and baited remote underwater video to study the behaviour of lobster at comparable sites. The density of legal-sized P. cygnus was twice as high within NTRs (0.34 ± 0.05) than fished sites (0.16 ± 0.03). P. cygnus also spent less time with bait in fished sites (0.42 ± 0.15 min) than NTRs (1.15 ± 0.28 min). This study provides the first evidence that behaviour of decapods, namely P. cygnus, is sensitive to noninjury-related disturbance associated with recreational fishing, with higher wariness in fished areas. Investigation is required into potentially confounding biotic and abiotic factors to further explore the applicability of lobster wariness as an indicator for fishing pressure.